Management Of Chronic Energy Deficiency (Ced) In Pregnant Women: Literature Review - Andriyani, Nur Syifa; Meiranny, Arum (Jurnal Maternitas Kebidanan, 2025)
Chronic Energy Deficiency (CED) in pregnant women is a condition experienced by pregnant women due to an imbalance in energy and protein nutritional intake, so that the substances needed by the body are not met. LiLA which is below 23.5 cm indicates that the pregnant woman has CED. This literature review aims to examine the management of CED in pregnancy by reviewing several research articles. This literature review method involves searching for articles using several databases via Google Scholar and Pubmed. Interventions that can be carried out include meeting nutritional needs and energy intake by providing additional foods high in calories and high in protein based on local ingredients.